Análise em redução de processamento redundante de energia em conversores de dois estágios para iluminação Led - Spode, Nelson da Silva (2018)
This work presents mathematics analysis, simulation and experimental results for two of the isolated converters, the forward and flyback, related to its potential concerning the realization of the reduced redundant power processing, or simply, R2P2. A publication from INMETRO establishes a series of technical requirements for LED based lighting systems. Some of the requirements are the compliance with IEC 61000-3-2 C Class, which limits the harmonic distortion for input current and, consequently, the power factor, as well as the compliance with CISPR15, which regulates the limits for electromagnetic interferences. These requirements, in special minimal luminous efficacy, suggest the use of R2P2 concept, because it can, theoretically, improve two stages drivers´ efficiency, and leads to reduction in size. Among the possible R2P2 basic configurations, the I-IIIB is the only one able to reduce the amount of reprocessed energy without degradation of power factor and THD. In this configuration, the power factor correction stage processes the entire input power and the second stage controls the energy to be delivered to the load and processes only a small fraction of the power supplied by the PFC stage. According to (SPIAZZI, 2016), many papers have been published and presented efficiency improvements in converters using the concept of R2P2 in a wrong way. The buck-boost converter would be the only non-isolated converter that could be connected in I-IIIB configuration due to the inverted output voltage. A meticulous analysis shows that a buck-boost converter in I-IIIIB configuration is, in fact, equivalent to a boost converter processing total output power, so it is a wrong implementation of R2P2 concept. The R2P2 implementation requires an isolated converter. A mathematical analysis, considering the conduction loss in circuit elements of forward and flyback converters is done normalized with respect to the boost converter processing all the load power and shows that it is theoretically possible to achieve better efficiency than a counterpart boost. The studies of cases presented here show that the isolated converters´ efficiencies are degraded when processing small energy due to the I-IIIB interconnection, and this affects R2P2 theorical benefits. Once the converters’ individual efficiencies are known, it is possible to calculate the maximum amount of energy that can be processed to achieve an increasing in efficiency. The executed tests, by simulation or by experimental prototypes, showed that only small improvements in efficiency are possible to achieve, on the other hand, smaller voltage stresses in components like output capacitors and diodes leads to advantages like smaller sizes or increased life cycles. Other aspects like reduction of overall converter size, cost and reliability could be taken into account to choose the R2P2 I-IIIB as an option for LED drivers.